2016
DOI: 10.1186/s12864-016-2685-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis revealed the drought-responsive genes in Tibetan hulless barley

Abstract: BackgroundHulless barley, also called naked barley, is an important cereal crop worldwide, serving as a healthy food both for human consumption and animal feed. Nevertheless, it often suffered from drought stress during its growth and development, resulting in a drastic reduction in barley yields. Therefore, study on molecular mechanism of hulless barley drought-tolerance is very important for increasing barley production. To investigate molecular mechanism of barley drought-resistance, this study examined co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…Transcriptome studies have shown that genes for heat shock proteins (chaperones), late-embryogenesis abundant (LEA) proteins, osmolyte biosynthesis, ROS scavenging, signal transduction, defense, and others are up-regulated in response to drought [3741]. These changes at the transcription level also increase accumulation of proteins and metabolites involved in drought resistance [4245].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome studies have shown that genes for heat shock proteins (chaperones), late-embryogenesis abundant (LEA) proteins, osmolyte biosynthesis, ROS scavenging, signal transduction, defense, and others are up-regulated in response to drought [3741]. These changes at the transcription level also increase accumulation of proteins and metabolites involved in drought resistance [4245].…”
Section: Introductionmentioning
confidence: 99%
“…thaliana, S. bicolor, and O. sativa. We phylogenetically analyzed the three genes SnRK2, PYR/PYL/RCAR, and ABF. These three drought-resistance related genes in Tibetan hulless barley were available in the literature of Zeng et al (2016). Interestingly, we observed that SnRK2, PYR/PYL/RCAR, and ABF of Tibetan hulless barley were all associated with the corresponding genes in B. distachyon under certain experimental conditions.…”
Section: Discussionmentioning
confidence: 63%
“…RNA-Seq of Himalaya 10 under different relative soil moisture content levels has been carried out previously (Zeng et al, 2016). Based on results of the ABA signaling pathway relevant to drought stress from the RNA-Seq data, we selected gene sequences of SnRK2, PYR/PYL/RCAR, and ABF from the RNA-Seq data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the induction is always a prediction for potential function (Wang et al , Yang et al , Zhao et al , Gao et al ) and upstream regulators such as the T. hispida eukaryotic translation initiation factor 1A ( TheIF1A ; Yang et al ), Phaseolus vulgaris Cd metal‐response element‐binding transcription factor 1 ( PvMTF‐1 ; Lin et al ), we can summarize that the drought‐inducing osmotic stress response of JrGSTTau1 is controlled by JrDREB2A , JrMYC2 , JrMYB44 , JrDof1 and JrWRKY7 , which may act as upstream regulators of JrGSTTau1 to either control JrGSTTau1 or act along with JrGSTTau1 to participate in plant drought stress response. Considering that the TFs of DREB, MYC, MYB, Dof and WRKY are members of a large family which have functions in plant osmotic stress responses, such as maize TaDREB3 (Shavrukov et al ), Tibetan hulless barley MYCs (Singh and Laxmi , Zeng et al ), Salicornia brachiata MYB44 (Shukla et al ), wheat TaMyb1D (Wei et al ), T. hispida Dof1.4 (Zang et al ), tomato SlCDF1‐5 (Corrales et al ), walnut JrWRKY7 and JrWRKY2 (Yang et al ). Therefore, based on these findings, we propose that the JrGSTTau1 gene is an important osmotic responsive gene and is involved in transcription pathways of DREB, MYC, MYB, Dof and WRKY.…”
Section: Discussionmentioning
confidence: 99%